STUDY ON THE INFLUENCE OF SHOT PEENING ON THE BENDING FATIGUE CHARACTERISTICS OF 20MNCR5 CARBURIZED GEAR - ZHAO HongQiao; XIAO JiSheng; ZHONG ZhenYuan; WANG Rong; LUO WeiXian; HU JianSun (Jixie qiangdu)
Bending fatigue failure is one of the main failure modes for gears in transmission system, shot peening is an important gear strengthen technology. In order to study the influence of shot peening on gear bending fatigue characteristics, 20 MnCr5 carburized involute cylindrical spur gear was adopted as study object. The effect of shot peening on gear surface integrity were analyzed before and after shot peening, coinciding with our products. Bending fatigue test was carried out with the single tooth loading method, afterwards, based on the observation of the failure fracture surfaces by scanning electron microscope（SEM）, the differences of failure characteristics in the crack source areas before and after shot peening were analyzed. It is found that shot peening can greatly improve gear surface integrity, although it has a negative effect on the gear surface corrugation. Shot peening can effectively increase gear bending strength and restrain the crack initiation from the gear surface.